Pengembangan Media Gambar Seri Berbasis Flipbook Untuk Menulis Narasi Pada Siswa Kelas IV SDN 9 Dungaliyo Kabupaten Gorontalo - Fadila Dai; Rusmin Husain; Wiwy Triyanty Pulukadang; Fidyawati Monoarfa; Ade Mahniar (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to develop flipbook-based serial picture media as an alternative instructional medium for narrative writing in Grade IV elementary school. The research employed Research and Development (R&D) methodology using the ADDIE model, involving 17 Grade IV students of SDN 9 Dungaliyo, Gorontalo Regency as trial subjects. Product validation was conducted by three expert validators encompassing media, language, and content experts. Aggregate validation results showed a feasibility percentage of 92.30% categorized as